The Effectiveness of Storybook on Students’ Reading Comprehension on First Grade Student of SMPN 2 Padang Panjang - Siska Willyani Putri; Yuli Tiarina (Journal of English Language Teaching, 2021)
Storybook is a book used for students to improve reading comprehension through pictures and color. The purpose of this research is to find out whether a storybook effective or not on students' reading comprehension. This research also aims to know students' opinions on storybooks for reading comprehension. This research was pre-experimental to evaluate the influence of a variable on one group by pre-test and post-test design. The population and sample of this research were 23 students on first-grade students of SMPN 2 Padang Panjang. This research used two instruments; reading comprehension test and student's opinion on storybooks for the reading comprehension questionnaire. The result shows that a storybook is effective on students’ reading comprehension.  The mean score on the pre-test was 48.22 and the mean score on the post-test was 83.66. The significant value of this research is 0.00. The Sig. (2-tailed) determines there is a significant difference from pre-test to post-test. Supported by students’ opinion on storybooks for reading comprehension questionnaire interpreted as strongly agree with the mean score total is 3.24. The mean score between 3,20 up to 4,00 indicated that a storybook is very good for reading comprehension. The totals mean score was 3.37 that can be interpreted as very good.